Adoption and Use of Software in Land Use Planning Practice: A Multiple-Country Study. Issue 1 (2nd January 2018) - Russo, Patrizia; Lanzilotti, Rosa; Costabile, Maria Francesca; Pettit, Christopher James
ABSTRACT: Planning Support Systems (PSS) are computer-based tools that assist professionals in land use planning activities. Although several researchers acknowledge the importance of such tools in planning practice, PSS use is limited due to their poor fit to users' needs and expectations as well as to their low usability. This article presents a study carried out in three different countries, namely, Australia, Italy, and Switzerland, aiming at investigating in-depth the current situation regarding the adoption of PSS and identifying factors preventing their wider use, devoting particular attention to the quality of such systems from the point of view of their users. The study also aimed at analyzing planners' expectations in order to identify relevant features that PSS should provide. The main part of the study consisted of 35 interviews with planning experts. A follow-up focus group with six further participants was also performed. The results confirmed some findings of previous studies but also revealed new insights. This article provides suggestions on how to address the emerging issues, as well as pathways for creating software that can be adopted and used with satisfaction in the planning practice.